Pregnancy with Hypertrophic Cardiomyopathy – A Potential Risk Factor for Maternal Mortality - Kumare, BD; Kawthalkar, A (Kathmandu University Medical Journal, 2015)
We report a case of a 21 year old married woman diagnosed to have severe hypertrophic cardiomyopathy at 12 weeks of gestation by echocardiograph at Lata Mangeshkar Hospital, Nagpur on 12th June, 2012. Her mother’s and maternal uncle’s sudden death at young age along with severe form of disease brought a lot of apprehension in the beginning considering the possible catastrophic effect of hemodynamic changes associated with pregnancy and labor. She was asymptomatic before pregnancy but developed dyspnoea on exertion during pregnancy and hence was started on calcium channel blocker verapamil. She remained asymptomatic throughout pregnancy and later underwent elective caesarean section at term under epidural anaesthesia for major cephalopelvic disproportion with uneventful postoperative course. Current data on pregnancy outcome in Hypertrophic cardiomyopathy are limited in Southasian countries despite its high prevalence in general population. This case report illustrates that with favourable clinical profile and specialist multidisciplinary team management women with hypertrophic cardiomyopathy tolerate pregnancy well with good outcome. Kathmandu Univ Med J 2013; 11(4): 335-337